Differential Neurobehavioral Effects of Cross-Modal Selective Priming on Phonetic and Emotional Prosodic Information in Late Second Language Learners. - Chieh Kao; Yang Zhang (Journal of Speech, Language & Hearing Research, 2020)
Purpose: Spoken language is inherently multimodal and multidimensional in natural settings, but very little is known about how second language (L2) learners undertake multilayered speech signals with both phonetic and affective cues. This study investigated how late L2 learners undertake parallel processing of linguistic and affective information in the speech signal at behavioral and neurophysiological levels. Method: Behavioral and event-related potential measures were taken in a selective cross-modal priming paradigm to examine how late L2 learners (N = 24, M = 25.54 years) assessed the congruency of phonetic (target vowel: /a/ or /i/) and emotional (target affect: happy or angry) information between the visual primes of facial pictures and the auditory targets of spoken syllables. Results: Behavioral accuracy data showed a significant congruency effect in affective (but not phonetic) priming. Unlike a previous report on monolingual first language (L1) users, the L2 users showed no facilitation in reaction time for congruency detection in either selective priming task. The neurophysiological results revealed a robust N400 response that was stronger in the phonetic condition but without clear lateralization and that the N400 effect was weaker in late L2 listeners than in monolingual L1 listeners. Following the N400, late L2 learners showed a weaker late positive response than the monolingual L1 users, particularly in the left central to posterior electrode regions. Conclusions: The results demonstrate distinct patterns of behavioral and neural processing of phonetic and affective information in L2 speech with reduced neural representations in both the N400 and the later processing stage, and they provide an impetus for further research on similarities and differences in L1 and L2 multisensory speech perception in bilingualism.